Effects of different stepwise reduction taper protocols on cycling performance - Neary, J. P.; Bhambhani, Y. N.; McKenzie, D. C. (Canadian Journal of Applied Physiology, 2003)
This study examined the effects of different 7-day taper protocols on simulated 20-km time trials (20TT). Following 3 weeks of baseline training, 11 male cyclists (.VO2max = 4.78 +/- 0.66 L.min-1) were randomly assigned to one of three stepwise reduction tapers in which training volume was reduced by 30% (T30, n = 5), 50% (T50, n = 6), or 80% (T80, n = 6) of baseline training with intensity (85% .VO2max) maintained. Cardiorespiratory measurements were collected every 5 km during the 20TT. Results revealed a significant (5.4%, 0.05) improvement in 20TT performance in the T50 protocol with concomitant increases in .VO2 and O2 pulse. No significant differences were found in T30 or T80. These results showed that a moderate (50%) reduction in weekly training volume appeared to be optimal in terms of enhancing performance. This confirms the contention that proper placement of training volume during tapering, while maintaining exercise intensity, can elicit performance improvements.